EVALUASI KESESUAIAN LAHAN PADI PADA SAWAH IRIGASI DI KECAMATAN JUNREJO KOTA BATU - Abel Fabyan Fernando Sareh; Mochtar Luthfi Rayes (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Rice is the most important food crop because most of the Indonesian population uses rice (processed rice grains) as a staple food to meet nutritional needs. Junrejo District is the main center for rice cultivation (irrigated rice fields) in Batu City. There is a variation in the production of irrigated rice in the District of Junrejo, so it is necessary to evaluate the suitability of the land to assess the potential or class of land suitability for the purpose of land use. The conditions for growing existing plants are not in accordance with the facts of production in the field, so it is necessary to modify the conditions for growing rice. The purpose of this study was to evaluate land suitability of rice on irrigated rice fields in Junrejo District of Batu. The characteristics of the land measured were pH H2O, organic-C, total-N, available-P, exchangeable-K, cation exchange capacity, base saturation, and soil texture. Land characteristics that have been analyzed were then matched. Modification of new plant growth requirements used the Boundary Line and Production Results equation. The results showed that the land suitability classes for each land mapping unit (LMU) in Junrejo District were as follows: S2 forÂ LMU 1, and S3 for LMU 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, and 13. The liming factors for each LMU were availability of nutrients (total-N, available-P, exchangeable-K), as wells as organic-C content and base saturation.